Pseudorabies gD protein protects mice and piglets against lethal doses of pseudorabies virus - Zhao, Mengpo; Chen, Jing; Luo, Shengjun; Yan, Renhe; Zhang, Pian; Ren, Zhaowen; Chen, Xiaofan; Wang, Gang; Xiang, Hua; Cai, Rujian; Huang, Yuan; Li, Na; et al. (Frontiers in Microbiology, 2023)
Pseudorabies (PR) is a highly contagious viral disease caused by the pseudorabies virus (PRV), which can cause disease in a wide range of domestic and wild animals. Studies have shown that new mutant strains have emerged in pig farms in many regions and that commercial inactivated and live attenuated vaccines are becoming less effective at protecting pigs.Methods: Porcine pseudorabies glycoprotein D (gD) gene (GenBank: QEY95774.1) with hexa-His tag to the C terminus for further purification processes was cloned into the lentiviral expression plasmid pLV-CMV-eGFP by restriction enzyme, the resulting plasmid was designated as pLV-CMV-gD. HEK-293T cells with robust and stable expression of recombinant gD protein was established by infection with recombinant lentivirus vector pLV-CMV-gD.we expressed porcine pseudorabies virus gD protein using HEK-293T cells.We describe in this study that individual gD proteins produced by a mammalian cell expression system are well immunogenic and stimulate high levels of PRV-specific and neutralizing antibodies in mice and piglets. All mice and piglets survived lethal doses of PRV, significantly reducing the amount of PRV virus in piglets' lymph nodes, lungs, spleen, and other tissues. It also significantly reduced the time cycle and amount of viral excretion from piglets to the environment through the nasal and anal cavities.The results suggest that PRV gD protein is expected to be a potential candidate for the preparation of genetically engineered PR vaccines for the prevention of PRV infection and the control of PR epidemics.